On the representation of solutions of delayed differential equations via Laplace transform - Pospíšil Michal; Jaroš František (2016)
In this paper, the unilateral Laplace transform is used to derive a closed-form formula for a solution of a system of nonhomogeneous linear differential equations with any finite number of constant delays and linear parts given by pairwise permutable matrices. This unifies the recent results on the representation of such solutions.